Combinatorial metallurgical synthesis and processing of high-entropy alloys. Issue 19 (14th October 2018) - Li, Zhiming; Ludwig, Alfred; Savan, Alan; Springer, Hauke; Raabe, Dierk
Abstract: Abstract : High-entropy alloys (HEAs) with multiple principal elements open up a practically infinite space for designing novel materials. Probing this huge material universe requires the use of combinatorial and high-throughput synthesis and processing methods. Here, we present and discuss four different combinatorial experimental methods that have been used to accelerate the development of novel HEAs, namely, rapid alloy prototyping, diffusion-multiples, laser additive manufacturing, and combinatorial co-deposition of thin-film materials libraries. While the first three approaches are bulk methods which allow for downstream processing and microstructure adaptation, the latter technique is a thin-film method capable of efficiently synthesizing wider ranges of composition and using high-throughput measurement techniques to characterize their structure and properties. Additional coupling of these high-throughput experimental methodologies with theoretical guidance regarding specific target features such as phase (meta)stability allows for effective screening of novel HEAs with beneficial property profiles.